2007
DOI: 10.1002/ejoc.200700810
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Active Catechol‐Functionalized Molecular Rods: Suitable Protection Groups and Single‐Molecule Transport Investigations

Abstract: The synthesis of molecular rod 1 comprising a central redox‐active unit and two terminal acetyl‐protected sulfur groups is reported. Various protecting groups for the catechol moiety were investigated and protected precursors 14–18 were synthesized. In particular, ethyl orthoformate 17 can be easily and selectively deprotected in mild acidic conditions ruling out the need for a strong Lewis acid like boron tribromide. The redox activity of 1 was confirmed by cyclic voltammetric investigations. Gold–molecule–go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 79 publications
4
40
0
Order By: Relevance
“…This value is the same order of magnitude as the conductance value obtained for other OPE derivatives using thiols as anchoring groups (1.8 10 À5 G 0 ). [48,49] Therefore, it is concluded that both the amino and trimethylsilane groups are alternative linkers that provide electronic coupling between the electrodes and the molecule which is essentially as efficient as that through thiols. However, outside the À0.6 to + 0.6 voltage range the response deviates from linearity showing a sigmoidal behaviour over the full voltage region.…”
Section: Resultsmentioning
confidence: 99%
“…This value is the same order of magnitude as the conductance value obtained for other OPE derivatives using thiols as anchoring groups (1.8 10 À5 G 0 ). [48,49] Therefore, it is concluded that both the amino and trimethylsilane groups are alternative linkers that provide electronic coupling between the electrodes and the molecule which is essentially as efficient as that through thiols. However, outside the À0.6 to + 0.6 voltage range the response deviates from linearity showing a sigmoidal behaviour over the full voltage region.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 17 :22 Compound 16 (19.2 g, 68.1 mmol) was dissolved in CH 2 Cl 2 (100 mL) and the solution was cooled to 0 °C. A solution of ICl (23.1 g, 0.14 mol) in CH 2 Cl 2 (100 mL) was added slowly.…”
Section: Methodsmentioning
confidence: 99%
“…Solvent was removed in vacuo and the residue was purified by flash chromatography (SiO 2 : hexane/CH 2 Cl 2 = 10:1) to give the product 16 as a colorless oil (82.5 g, 89 %). 1 Compound 17: [22] Compound 16 (19.2 g, 68.1 mmol) was dissolved in CH 2 Cl 2 (100 mL) and the solution was cooled to 0 8C. A solution of ICl (23.1 g, 0.14 mol) in CH 2 Cl 2 (100 mL) was added slowly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Among other possible architectures, thiols with redox-active tail groups (e.g., ferrocenyl, [7][8][9][10][11][12][13] ruthenocenyl, [14] or other [15][16][17] moieties) can be used as potential candidates for SAM formation on suitable substrates (e.g., coinage metals or GaAs). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The corresponding molecular films can then be used in different electrochemical applications with the substrate itself acting as a positive or negative electrode depending on the need.…”
Section: Introductionmentioning
confidence: 99%